In Silico Study of Kaempferol Targeting MMPs and COX-2 for Anti-Aging and Wound Healing - Theodorus Rexa Handoyo (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2025)
Skin aging and impaired wound healing are complex biological processes involving chronic inflammation and excessive degradation of the extracellular matrix. Matrix metalloproteinases (MMP-1, MMP-3, and MMP-9) and cyclooxygenase-2 (COX-2) play crucial roles in these processes and are considered important molecular targets for anti-aging and wound healing therapies. Kaempferol is a natural flavonoid compound known for its antioxidant and anti-inflammatory activities; however, its molecular interaction mechanisms with these targets remain incompletely understood. This study aimed to evaluate the potential of kaempferol as an anti-aging and wound healing agent through a molecular docking approach targeting MMP-1, MMP-3, MMP-9, and COX-2. Molecular docking simulations were performed using Molegro Virtual Docker 6.0, while ligand-protein interactions were visualized and analyzed using BIOVIA Discovery Studio Visualizer v.21.1.0.20298. The docking results indicated that kaempferol exhibited favorable binding affinities toward all target proteins, with the strongest interactions observed for MMP-9 and COX-2. Kaempferol formed conventional hydrogen bonds as well as hydrophobic and aromatic interactions within the active sites of the proteins. In conclusion, kaempferol demonstrates potential as a multitarget natural compound for anti-aging and wound healing applications, although further in vitro and in vivo studies are required to validate its biological activity.